UPS-Tailored Next-Generation Battery Technologies: Variability, Sustainability, Comparative Analysis and a Technology Roadmap - S., Manoharan; B., Mahalakshmi; P., Sindhu M; R, Vidyalakshmi; K., Anandhi; K., Gaayathry (Journal of Trends in Computer Science and Smart Technology, 2025)
The global uninterruptible power supply forecast market is estimated at nearly USD 4.04 billion in 2024 owing to the growth in demand at data centers and other crucial sectors. Despite the great deal of information available in battery research, most of the literature on uninterruptible power supply does not consider the variability (temperature, depth of discharge, duty cycle) and mode of operation (grid-interactive vs. Standalone) performance during other operational modes. This review overcomes these deficiencies by providing three contributions: (1) variability in uninterruptible power supply specific quantitative performance metrics; (2) a growth map predicting the adoption of various battery chemistries in UPS on a short, medium, and long-term basis; (3) a sustainability assessment through the lens of primary materials, recyclability, and costs from the life cycle. Representative outcomes include: low-cost standby solutions from VRLA batteries, but limited cycle life (500–1,500 cycles); continuous UPS applications are dominated by LFP and LTO chemistries, which have a high tolerance to deep cycles; Li–S batteries have a high energy density (350–600 Wh/kg), but poor cycle life (10,000 cycles) and are still too bulky for compact uninterruptible power supply systems. These conclusions provide a reasonable assessment of the cross technology trade-offs and the underlying research gaps to derive a pathway towards next generation reliable UPS batteries.
Keywords: UPS; Battery Technologies; Lithium-Ion; Sodium-Ion; Solid-State Batteries; BMS; Sustainability; Hybrid Systems; Thermal Management